2021
DOI: 10.3390/catal11030361
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Performance of Cerium-Based Catalysts for Selective Catalytic Reduction of Nitrogen Oxides: A Critical Review

Abstract: Selective catalytic reduction of nitrogen oxides with NH3 (NH3-SCR) is still the most commonly used control technology for nitrogen oxides emission. Specifically, the application of rare earth materials has become more and more extensive. CeO2 was widely developed in NH3-SCR reaction due to its good redox performance, proper surface acidity and abundant resource reserves. Therefore, a large number of papers in the literature have described the research of cerium-based catalysts. This review critically summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 118 publications
0
14
0
Order By: Relevance
“…There is also evidence for oxygen release by Ce in the structure of Fe 3 O 4 via the redox shift in between the Ce 4+ and Ce 3+ leading to charge compensating vacancies. [ 58 ] Overall, it can be concluded that the effect of Ce–Fe 3 O 4 nanoparticles on curing reaction of epoxy should be reflected in higher Δ H and consequently denser epoxy crosslinked network. To prove this, we capture the fingerprint of crosslinking of blank epoxy and epoxy nanocomposite systems for the sake of comparison.…”
Section: Resultsmentioning
confidence: 99%
“…There is also evidence for oxygen release by Ce in the structure of Fe 3 O 4 via the redox shift in between the Ce 4+ and Ce 3+ leading to charge compensating vacancies. [ 58 ] Overall, it can be concluded that the effect of Ce–Fe 3 O 4 nanoparticles on curing reaction of epoxy should be reflected in higher Δ H and consequently denser epoxy crosslinked network. To prove this, we capture the fingerprint of crosslinking of blank epoxy and epoxy nanocomposite systems for the sake of comparison.…”
Section: Resultsmentioning
confidence: 99%
“…The acidic sites are active for ammonia adsorption and the rate determining step of the reaction of adsorbed ammonia (on either a Brønsted or Lewis acid site) with NO from the gas phase [131,132]. The method of catalyst preparation and incorporation of cerium into the catalyst was also shown to greatly affect cerium promotion [133] with the following order found for efficacy: hydrothermal treatment > sol-gel > co-precipitation > impregnation > mechanical mixing [134]. This order was attributed to maximizing the interaction of the catalyst components to enhance overall surface and lattice oxygen mobility as well as creating the surface acid sites necessary for the adsorption of the reactants.…”
Section: No X Remediationmentioning
confidence: 99%
“…For metal-based catalysts, many reviews focused on Mnbased oxides catalysts, [44][45][46][47] Ce-based oxides catalysts, 48 Febased oxides 49 and the CeO x -MnO x mixture catalysts 50 were published as those catalysts exhibited excellent lowtemperature (<100 C) in NH 3 -SCR. In addition, the latest progress on the vanadia-based and vanadia-free metal oxides catalysts had also been summarized.…”
Section: Introductionmentioning
confidence: 99%